2020
DOI: 10.1093/jpids/piaa024
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rifampin Concentrations by Urine Colorimetry and Mobile Phone Readout for Personalized Dosing in Tuberculosis Treatment

Abstract: Background Individual pharmacokinetic variability is a driver of poor tuberculosis (TB) treatment outcomes. We developed a method for measurement of rifampin concentrations by urine colorimetry and a mobile phone photographic application to predict clinically important serum rifampin pharmacokinetic measurements in children treated for TB. Methods Among spiked urine samples, colorimetric assay performance was tested with conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“… 5–7 , 34 Anti-TB drug concentration testing in saliva complements other non-invasive tests, such as colorimetric assays recently developed in urine, which may expand access to personalized dosing not only for those people with TB distant from referral laboratories but also for populations such as children and/or those severely malnourished or with poor venous access where multiple blood draws will be relatively contraindicated or technically difficult. 35 , 36…”
Section: Discussionmentioning
confidence: 99%
“… 5–7 , 34 Anti-TB drug concentration testing in saliva complements other non-invasive tests, such as colorimetric assays recently developed in urine, which may expand access to personalized dosing not only for those people with TB distant from referral laboratories but also for populations such as children and/or those severely malnourished or with poor venous access where multiple blood draws will be relatively contraindicated or technically difficult. 35 , 36…”
Section: Discussionmentioning
confidence: 99%
“…We were successfully able to quantify levofloxacin in urine with a spectrophotometer using colorimetric principles. Although urine has been used for testing the presence of some first-line TB drugs using colorimetry, [ 11 , 14 ] to the best of our knowledge, this is the first time levofloxacin has been quantified in urine by colorimetric principles obtained from healthy participants after levofloxacin administration and patients living with HIV treated with levofloxacin for MDR-TB. The area under the ROC curve was >0.8 in the derivation as well as the validation study, which demonstrates that this assay performs well in predicting clinically important serum targets.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ] Application of urine colorimetry for assessment of rifampicin PK/PD targets has been successful. [ 11 ] Thus, we modified a previously described assay for fluoroquinolone concentration measurement by urine colorimetry, examined its performance over a 24 h dosing interval of levofloxacin excretion, and assessed its ability to predict clinically relevant serum PK/PD targets from PLWH and taking levofloxacin for MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…Our survey showed that progress in TDM is being made, with half of the survey participants using TDM. Cheaper and easy to use assays [9][10][11], clinical guidelines [2][3][4] and laboratory quality control standards [12] are all increasing in availability. However, the main challenge is a lack of widespread information about TDM, with progress being recognised by participants who look towards guidelines and research when performing TDM.…”
Section: Https://isgd/tdmsurveymentioning
confidence: 99%